2018
DOI: 10.14687/jhs.v15i3.5414
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of graduate research on English preparatory programs at universities

Abstract: This study examines master’s and doctoral theses on English preparatory classes at tertiary level in Turkey in terms of completion year, thesis type, subject areas, data types, research design, sample groups, problem statements and recommendations. This study is a systematic review of literature and the data was collected through document analysis technique. Content analysis was carried out on the theses selected through criterion sampling method. A total of 82 theses, which were completed by July 2017, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Koçyiğit and Erdem (2018) undertook a study to review English preparation classes in higher education considering the graduate research. Their study found that these studies usually employed a quantitative research design and they generally focused on students' perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Koçyiğit and Erdem (2018) undertook a study to review English preparation classes in higher education considering the graduate research. Their study found that these studies usually employed a quantitative research design and they generally focused on students' perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The observed problem that makes the researcher conduct this study is that there are some studies focusing on the content analysis of the articles related to (a) foreign language education in Turkey in general (Alptekin & Tatar, 2011;Solak, 2014;Yağız, Aydın & Akdemir, 2016), (b) English language teacher education (Avalos, 2011;Demir & Koçyiğit, 2018;Kleinsasser, 2013;Vélez-Rendón, 2002), (c) strategy training in L2 learning (Mutlu, 2015), (d) graduate research on ELT in Turkey (İnal, Özdemir, Kıray & Oral, 2016;Koçyiğit & Erdem, 2018;Özmen, Cephe, & Kınık, 2016), (e) teaching English with technology (Hussein, 2015), (f) using flipped classroom in foreign language education (Ahmed & Asiksoy, 2018;Filiz & Benzet, 2018), (g) assessment and evaluation in foreign language teaching in Turkey (Arslan & Kartal, 2018), (h) teaching L2 listening (Dewitt-Brinks & Rhodes, 1992) and (i) teaching L2 reading (Akaydın & Cecen, 2015;Parsons & Gallagher, 2016) in the literature. However, there are no research studies regarding the content analysis of the articles related to teaching L2 pronunciation.…”
Section: Purpose and Problemmentioning
confidence: 99%